2017
DOI: 10.1016/j.urolonc.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of noninvasive urine tests for ruling out recurrent urothelial carcinoma

Abstract: The Cxbladder Monitor test significantly outperforms current Food and Drug Administration-approved urine-based monitoring tests, as well as cytology, in a large representative population undergoing surveillance for recurrent UC. This supports using Cxbladder Monitor as a confirmatory negative adjunct to cystoscopy or to justify postponing cystoscopic investigations in patients with a low risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 28 publications
6
95
1
1
Order By: Relevance
“…According to a phased approach, NMP22 tests reached phase III (independent confirmation studies). Recently, four marker-comparison studies have been published, reporting low sensitivity rates of the qualitative test in detecting Rec (11–58%) [7, 1820]. In contrast, the quantitative NMP22BC test is measured on a continuous scale and then transformed into a dichotomous variable by choosing a cut-off threshold (estimated at 10 ng/mL).…”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%
See 2 more Smart Citations
“…According to a phased approach, NMP22 tests reached phase III (independent confirmation studies). Recently, four marker-comparison studies have been published, reporting low sensitivity rates of the qualitative test in detecting Rec (11–58%) [7, 1820]. In contrast, the quantitative NMP22BC test is measured on a continuous scale and then transformed into a dichotomous variable by choosing a cut-off threshold (estimated at 10 ng/mL).…”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%
“…From a biologic point of view, the use of a cut-off does not make much sense in the context of the continuity that the appearance of this marker represents, and therefore, generally leads to lower overall accuracy. Indeed, NMP22 BladderChek had a very poor sensitivity level for detecting Rec (26%), which only slightly outperformed that obtained with NMP22BC in the same population [7]. However, in a decision curve analysis, NMP22 was associated with oncological outcomes; it has been suggested that this test could be useful in decision-making between an immediate and delayed cystoscopy, depending on a clinician’s threshold to perform a surveillance cystoscopy [21].…”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Urine cytology is the standard non-invasive urine test that relies on visual inspection of abnormal cells in patient's urine under a microscope [41,42]. However, it is limited by its low sensitivity, especially in the detection of low-stage, low-grade bladder cancer [40,[63][64][65]. For such bladder tumors in early stages of development, the sensitivity of cytology is approximately 20% [66,67].…”
Section: Non-invasive Techniquesmentioning
confidence: 99%
“…Furthermore, histological examinations have limited ability for prognostication as they do not reflect biological behaviour of the tumor, merely physical appearance [44]. High levels of inter-observer, intra-observer, and institutional variability also reduce the reliability of urine cytology results [40]. In addition, cytology requires highly trained personnel for sample evaluation, who may not be available in all areas [68].…”
Section: Non-invasive Techniquesmentioning
confidence: 99%